Analisis Harga Saham Terhadap Efisiensi Pasar Modal Dimasa Pandemi Covid-19 Periode 2019-2020 - Dwi Urip Wardoyo; Riza Permata Octavianty; Rangga Wishnu Wardhana (CV. Ulil Albab Corp, 2022)
The capital market is a place where companies or other institutions meet where the funds come from the public for business development, expansion, and other capital additions. This study aims to determine the effect of stock prices on the efficiency level of the capital market before and after the COVID-19 pandemic period 2019-2020. The method used in this research is quantitative method. The type of research in this research is descriptive. The population in this sample is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020. The sampling technique in this study uses a purposive sampling technique from secondary data taken through the idx.co.id site. In this study using the paired t test sample test model. The results of this study indicate that there is an influence of stock prices on capital market efficiency during the covid-19 pandemic, namely the difference in stock prices in consumer goods industrial sector companies before and after the first positive case of Covid-19 in Indonesia was announced. Meanwhile, from the perspective of the consumer goods industry sector, not all companies in the consumer goods industry sector listed on the Indonesia Stock Exchange have differences or changes in share prices in companies. in the consumer goods industry after the COVID-19 pandemic.